2009
DOI: 10.1007/s11259-009-9308-2
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of dogTERT in canine testicular tumours in relation to PCNA, ki67 and p53 expression.

Abstract: The objective of the study was to determine the immunohistochemical expression of canine TERT in canine testicular tumours comparing two different antibodies for TERT, and to correlate them with well established markers specific to dividing cells such as PCNA and ki67, and with expression of the p53 tumour suppressor gene. The study included 36 cases of canine testicular tumours, which were categorized as 12 Sertoli Cell Tumours (SCT), 20 seminomas, 3 interstitial cell tumours and 1 mixed germ cell-sex cord st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…In dogs, PCNA was recognized as a useful proliferation marker being associated with recurrence after surgical treatment in mammary tumours and in mast cell tumours . Meanwhile, other authors reported no correlation with prognosis, recurrence or metastasis in testicular as well as in mammary tumours . To the authors' knowledge, PCNA's prognostic value has never been evaluated in canine OSCC.…”
Section: Discussionmentioning
confidence: 93%
“…In dogs, PCNA was recognized as a useful proliferation marker being associated with recurrence after surgical treatment in mammary tumours and in mast cell tumours . Meanwhile, other authors reported no correlation with prognosis, recurrence or metastasis in testicular as well as in mammary tumours . To the authors' knowledge, PCNA's prognostic value has never been evaluated in canine OSCC.…”
Section: Discussionmentioning
confidence: 93%
“…Both canine and male seminomas showed the strongest expression of Ki-67 in all testicular tumors analyzed in our study, however, with only slightly weaker immunoreactivity in Leydig cell tumors. Also Papaioannou et al showed that the nuclear expression of Ki-67 is the strongest in seminomas, and somehow weaker in other types of canine testicular tumors [43]. The usefulness of Ki-67 antigen as a marker of cell proliferation was also confirmed in human testicular germ cell tumors [44].…”
Section: Discussionmentioning
confidence: 99%
“…Samples from the duodenum, the jejunum, the ileum and the cecum were evaluated for cell proliferation according to the method described by Papaioannou et al (2009) . Fixed tissues were embedded in paraffin wax and serial sections (4–6 µ m) were cut.…”
Section: Methodsmentioning
confidence: 99%